Molecular mechanism of sulphonylurea block of K(ATP) channels carrying mutations that impair ATP inhibition and cause neonatal diabetes. - Proks, P; De Wet, H; Ashcroft, F (2013)
Sulphonylurea drugs are the therapy of choice for treating neonatal diabetes (ND) caused by mutations in the ATP-sensitive K(+) channel (KATP channel). We investigated the interactions between MgATP, MgADP, and the sulphonylurea gliclazide with KATP channels expressed in Xenopus oocytes. In the absence of MgATP, gliclazide block was similar for wild-type channels and those carrying the Kir6.2 ND mutations R210C, G334D, I296L, and V59M. Gliclazide abolished the stimulatory effect of MgATP on all channels. Conversely, high MgATP concentrations reduced the gliclazide concentration, producing a half-maximal block of G334D and R201C channels and suggesting a mutual antagonism between nucleotide and gliclazide binding. The maximal extent of high-affinity gliclazide block of wild-type channels was increased by MgATP, but this effect was smaller for ND channels; channels that were least sensitive to ATP inhibition showed the smallest increase in sulphonylurea block. Consequently, G334D and I296L channels were not fully blocked, even at physiological MgATP concentrations (1 mmol/L). Glibenclamide block was also reduced in β-cells expressing Kir6.2-V59M channels. These data help to explain why patients with some mutations (e.g., G334D, I296L) are insensitive to sulphonylurea therapy, why higher drug concentrations are needed to treat ND than type 2 diabetes, and why patients with severe ND mutations are less prone to drug-induced hypoglycemia.